APLIKASI PENGOLAHAN DATA RENTAL MOBIL BERBASIS ANDROID (STUDI KASUS : PRAJA RENTAL JAMBI): Application, Ordering, Car Rental, Mobile. - Simorangkir, Lucy; Furnawan, Hambali; Saputra, Joni (LP2M Universitas Nurdin Hamzah, 2018)
Rental Praja is one of the Rental which is engaged in providing car rental services, which experience intense competition with similar rentals. For this reason, this rental is trying to improve the quality of its services so that it is not left by its customers. One effort that can be done so that the data processing process can be done better and get maximum results is by using an Android-based application. This study aims to assist Rental District in providing services to customers and providing car information and car booking transactions. This system is built using PHP Programming Languages ​​and MySQL databases. Inputs from this application are vehicle data, order data, confirmation data, transaction data, and category data. While the output is in the form of transaction data reports, confirmation data reports, order data reports and order details that customers will receive. The results show that this Car Rental Application is expected to be more helpful in Rental Cars especially in Mobile car rental booking transactions.